PENGARUH WAKTU TUNGGU HASIL PEMERIKSAAN LABORATORIUM TERHADAP EFEKTIVITAS PELAYANAN PASIEN DI PUSKESMAS KEDIRI KABUPATEN LOMBOK BARAT TAHUN 2024 - Ajely Rani Marlina; Abdul Aziz Fatryawan (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2024)
In laboratory services at the Kediri Health Center, patients still often complain about the long wait for laboratory test results. Then based on field observations, laboratory equipment is insufficient and human resources are limited. In addition, the number of patients who carry out examinations reaches 30 to 40 people per day. This can cause the laboratory service time to be long. This study aims to determine the effect of Wakttu Wait for Laboratory Examination Results on the effectiveness of services at the Kediri Health Center, West Lombok Regency. This research was carried out for 3 months starting from March to May 2023 using the cross sectional method. The number of respondents as a sample was 97 people determined by accidental sampling. Data were collected in the analysis using univariate analysis and bivariate analysis The results showed that (1) The waiting time > 140 minutes obtained laboratory results for 34 patients (35.1%) and patients with a fast waiting time of ≤ 140 minutes received laboratory results at the Kediri Health Center, West Lombok Regency amounting to 63 people (64.9%), (2) Patients who felt that the effectiveness of laboratory staff services was less effective amounted to 31 people (32.0%), while patients who felt that the effectiveness of laboratory staff services were effective at the Kediri Regency Health Center West Lombok amounted to 66 people (68.0%) (3) The waiting time for patients to get laboratory results that is relatively long > 140 minutes amounted to 34 people, of which 24 people (70.6%) felt that the effectiveness of the service was less effective as many as 10 people (29.4%). The waiting time to get laboratory results that was relatively fast ≤ 140 minutes amounted to 63 people, of which 7 people (11.1%) felt that the service effectiveness was less effective as many as 56 people (88.9%). From the results of the statistical test, the p-value (Asymptotic Significance) of Pearson Chi Square = 0.000 < α 0.05 (Significant) was obtained. This means that there is an effect on the waiting time for laboratory examination results on the effectiveness of laboratory officer services at the Kediri Health Center, West Lombok Regency in 2024.